Interpretation Of Democratic Ideas and Principles in The West and East (Eurasian Journal of Humanities and Social Sciences, 2024)
This article analyzes the interpretation of democratic ideas and principles in the West and the East. In particular, the article is based on the scientific analysis of the fact that in the West, democracy is primarily focused on the development of technologies based on the person and his interests, rights and freedoms, and in the democratic values of the East, democracy is based on the ideas of equality, freedom and tolerance of social and social groups.